Effects of Five Host Plant Species on the Life History and Population Growth Parameters of Myzus persicae (Hemiptera: Aphididae). Issue 5 (14th October 2019) - Hong, Feng; Han, Hong-Liang; Pu, Po; Wei, Dong; Wang, Jia; Liu, Yinghong
Abstract: The green peach aphid, Myzus persicae Sulzer (Hemiptera: Aphididae), is an important agricultural pest with a wide range of host plants. To study effects of host species on the life history traits of M. persicae, aphids were individually reared on five host plants: Brassica campestris L. (Brassicales: Brassicaceae), Capsicum annuum L. (Tubiflorae: Solanaceae), Nicotiana tabacum L. (Tubiflorae: Solanaceae), Raphanus sativus L. (Brassicales: Brassicaceae), and Vicia faba L. (Rosales: Leguminosae). TWOSEX-MSchart software was used for the statistical analysis according to the age-stage, two-sex life table theory. The results showed that the shortest preadult stage and adult/total prereproductive period of M. persicae were 6.48, 0.19, and 6.67 d on V. faba, respectively. While the adult and total longevity of M. persicae on R. sativus (25.00 and 31.62 d) and N. tabacum (24.40 and 30.56 d) were significantly longer than that on the other three hosts, as was the reproductive period. The fecundity of M. persicae on R. sativus (80.83 nymphs per female), N. tabacum (71.72 nymphs per female), and V. faba (70.39 nymphs per female) was also greater than that on B. campestris and C. annuum . It was demonstrated that V. faba, R. sativus, and N. tabacum were more suitable plants for the growth of M. persicae exhibiting a shorter preadult stage, longer longevity, and greater fecundity than the remaining two species, as confirmed by the higher intrinsic rate of increase and net reproductive rate.